Bank Market Structure and Firm Capital Structure - Lieven Baert; Rudi Vander Vennet (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We explore the impact of concentration in the banking markets on the capital structure of publicly quoted non-financial firms in the EU15 over the period 1997- 2005, an era marked by intensive merger activity in the banking sector. Our main finding is a negative and significant relationship between the degree of concentration of European bank markets and the market leverage of firms, indicating the persistence of credit constraints. This finding is robust when we use behavioral measures of bank conduct. This support for the market power hypothesis indicates that further measures are needed to make bank lending more competitive.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: G21; G32; 330; Bank concentration; Capital structure